(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
There are usually four lumbar arteries on each side, right and left, arising from the posterolateral aspect of the abdominal aorta1. Occasionally, a fifth lumbar artery may be seen arising from the median sacral artery. Above the bifurcation of the aorta, it gives rise to the median sacral artery from its posterior aspect, and the common iliac artery gives origin to the iliolumbar artery. [1] The four lumbar arteries run posterolaterally on the bodies of the first four lumbar vertebrae, pass posterior to the sympathetic trunk between the lumbar transverse processes, and then continue into the muscles of the anterior abdominal wall. [1,2] The first and second lumbar arteries on the right side, and the first lumbar artery on the left side, pass posterior to the right and left crura of the diaphragm respectively. [6] These vessels anastomose with each other and with the subcostal, iliolumbar, lower posterior intercostal, deep circumflex iliac and inferior epigastric arteries, ultimately supplying the muscles, ligaments, fasciae, joints, vertebrae and intervertebral discs of the lumbar region. [1]